Sustainability of Artistic Rural Revitalization: A Multiparty Collaborative Model Centered around Social Organizations with Zhujia Village in Nanjing as an Example - Dongting Bao; Tingting Chen (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
With the diversification of rural construction forms and increasing expectations on rural life improve-ment, artistic rural construction has gradually developed and is being practiced in China. To accurately guide the development and optimization of art rural construction, this study summarizes art intervention implementation methods in rural construction into four categories: NPO (Non-profit Organization) led, government led, enterprise led, and multiagency cooperation centered around social organizations. By taking Zhujia Village in Shijiu Lake, Nanjing as a typical case, this study delves into the process of a central social organization settling into the rural area, the role and participation of various entities in the rural construction process, and the effectiveness of rural construction implementation in material and cultural aspects. The “Zhujia Village” cooperation model is used to inspire theoretical research and empirical art intervention application paradigms in rural construction.